A Death-associated Protein Kinase (DAPK)-interacting Protein, DIP-1, Is an E3 Ubiquitin Ligase That Promotes Tumor Necrosis Factor-induced Apoptosis and Regulates the Cellular Levels of DAPK - Jin, Yijun (2002)
Death-associated protein kinase (DAPK) is a multi-domain Ser/Thr protein kinase with an important role in apoptosis regulation. In these studies we have identified a DAPK-interacting protein called DIP-1, which is a novel multi-RING finger protein. The RING finger motifs of DIP-1 have E3 ligase activity that can auto-ubiquitinate DIP-1 in vitro. In vivo, DIP-1 is detected as a polyubiquitinated protein, suggesting that the intracellular levels of DIP-1 are regulated by the ubiquitin-proteasome system. Transient expression of DIP-1 in HeLa cells antagonizes the anti-apoptotic function of DAPK to promote a caspase-dependent apoptosis. These studies also demonstrate that DAPK is an in vitro and in vivo target for ubiquitination by DIP-1, thereby providing a mechanism by which DAPK activities can be regulated through proteasomal degradation.